Contribution to the Ophioninae (Hymenoptera: Ichneumonidae) of Iran with the description of 16 new species and an illustrated key to the Eremotylus of the Western Palaearctic - Johansson, Niklas; Ameri, Ali; Riedel, Matthias; Talebi, Ali Asghar; Ebrahimi, Ebrahim (Zootaxa, 2021)
In this study, material of Iranian Ophioninae was examined. In total, 63 species are recognized as occurring in Iran. Sixteen species are described as new to science: Enicospilus amerii Johansson sp. nov., E. apocalypticus Johansson sp. nov., E. haladai Johansson sp. nov., Enicospilus peri sp. nov., Ophion al Johansson sp. nov., Ophion angustigena Johansson sp. nov., Ophion breviflagellator Johansson sp. nov., Ophion golestanicus Johansson sp. nov., Ophion klimenkoi Johansson sp. nov., Ophion persicus Johansson sp. nov., Ophion schmidti Johansson sp. nov., Ophion sinuosus Johansson sp. nov., Ophion sistanicus Johansson sp. nov., Ophion transcarinatus Johansson sp. nov., Ophion vasi Johansson sp. nov. and Ophion xrafstra Johansson sp. nov. Sixteen species: Enicospilus combustus (Gravenhorst, 1829); E. intermedius (Johansson, 2018); E. undulatus (Gravenhorst, 1829); Ophion angularis Johansson & Cederberg, 2019; Ophion bipictor Aubert, 1980; Ophion crassicornis Brock, 1982; Ophion confusus Johansson, 2019; Ophion ellenae Johansson, 2019; Ophion eremita Kokujev, 1906; Ophion kallanderi Johansson, 2019; Ophion rostralis Meyer, 1935; Ophion rufoniger Kohl, 1905; Ophion semipullatus Kokujev, 1909; Ophion tenuicornis Johansson, 2019; Hellwigiella dichromoptera (Costa, 1886) and Eremotylus curvinervis (Kriechbaumer, 1878) are new records for the fauna of Iran. Enicospilus flavocephalus (Kirby, 1900), Enicospilus monostigma (Vollenhoven, 1879) and Eremotylus sibiricus Szépligeti, 1905 are excluded from the Iranian checklist due to previous misidentifications. Enicospilus tarsalis Hedwig, 1957 syn. nov. is excluded from synonymy with E. ahngeri and instead introduced as a junior synonym of E. cruciator Viktorov, 1957. Enicospilus affinis Hedwig, 1957 stat. rev. is excluded from synonymy with E. ocellatus Shestakov, 1926 and reinstated as a valid species. Enicospilus splendidus Rousse, Soliman & Gadallah, 2017 syn. nov. is a junior synonym of Enicospilus stenopsis Kohl, 1905. Enicospilus grandiflavus Townes & Townes, 1973 (= E. grandis Morley) syn. nov. is synonymized with Enicospilus unicallosus (Vollenhoven, 1878). Enicospilus contributus Shestakov, 1926 is confirmed as a junior synonym of E. merdarius (Gravenhorst, 1829). Ophion fossulatus Hedwig, 1957 stat. rev. is excluded from synonymy with Ophion mocsaryi Brauns, 1899 and reinstated as a valid species close to Ophion parvulus Kriechbaumer. Ophion mocsaryi var. decedens Hedwig, 1961 syn. nov. is a synonym of Ophion bipictor Aubert, 1980. Ophion obscuratus var. heratensis Hedwig, 1961 syn. nov. is treated as a synonym of Ophion turcomanicus Szépligeti, 1905. Ophion pravinervis Kokujev, 1906, previously only known from the lost type collected in Georgia, is redescribed. Despite the relatively high number of new species here presented, the Iranian fauna most likely still harbours additional species awaiting discovery.